1984
DOI: 10.1007/bf00279303
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of complement C6 and haplotype analysis between C6 and C7 in a Japanese population

Abstract: Genetic polymorphism of C6 in the Japanese population has been described using polyacrylamide gel isoelectric focusing electrophoresis followed by the electrophoretic blotting technique, and haplotype analysis between C6 and C7 has also been investigated. In 565 plasma samples five different common patterns and three rare variant patterns were observed, and these were controlled by autosomal codominance at a single locus with three common and one rare alleles. These alleles were designated C6*B, C6*A, C6*B2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Nakamura and his colleagues described a result of an association analysis between C6 and C7 in a Japanese population. They suggested that two combinations between C6 and C7 alleles are in positive linkage disequilibrium (Nakamura et al, 1984b). However, Tokunaga et al (1986) found no evidence of linkage disequilibrium between C6 and C7 alleles in a haplotype study with 135 genotyped families.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Nakamura and his colleagues described a result of an association analysis between C6 and C7 in a Japanese population. They suggested that two combinations between C6 and C7 alleles are in positive linkage disequilibrium (Nakamura et al, 1984b). However, Tokunaga et al (1986) found no evidence of linkage disequilibrium between C6 and C7 alleles in a haplotype study with 135 genotyped families.…”
Section: Resultsmentioning
confidence: 98%
“…The allele C6"B3 was suggested to be the fourth common allele in a western Japanese population (Nishimukai et al, 1985). Nevertheless, it seems to be rare in Chinese populations as in eastern Japanese (Tokunaga et al, 1983(Tokunaga et al, , 1984Nakamura et al, 1984b).…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of the major C7 allele (C7*l) is 0.87 in Japanese [2,3] and 0.99 in Caucasians [1]. The frequency of the major C6 allele (C6*A) is 0.65 in Cauca sians [1,25] and 0.45 in Japanese [3,16,26]. In Japanese C6*B (0.48) is as frequent as C6*A [3,16,26].…”
Section: Discussionmentioning
confidence: 99%
“…The C7 gene is normally present as a single copy in the human genome and linked to the C6 gene [1], A maximum lod score of 8.43 was deter mined for this very close linkage [3], The gene arrangement for the C6 and C7 loci which are within a few kilobases is: 5'-C7-C6-3' [15], A positive linkage disequilibrium was suggested by Nakamura et al [16], which, however, was not confirmed by oth ers [3,4,17]. It has been considered that the complement proteins C6 and C7 have arisen by gene duplication [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in many populations revealed the existence of two common alleles (C6*A and C6*B) and a number of variant alleles, of which C6*B2 is polymorphic in Mongoloids [12][13][14]. C6 is closely linked to C7, the seventh component of complement, on chromosome 5 [15,16].…”
Section: Introductionmentioning
confidence: 99%